Pretrial Detention and the Value of Liberty - Mayson, Sandra G. (2021)
How dangerous must a person be to justify the state in locking her up for the greater good? The bail reform movement, which aspires to limit pretrial detention to the truly dangerous—and which has looked to algorithmic risk assessments to quantify danger—has brought this question to the fore. Constitutional doctrine authorizes pretrial detention when the government’s interest in safety “outweighs” an individual’s interest in liberty, but it does not specify how to balance these goods. If detaining ten presumptively innocent people for three months is projected to prevent one robbery, is it worth it? This Article confronts the question of what degree of risk justifies pretrial preventive detention if one takes the consequentialist approach of current law seriously. Surveying the law, we derive two principles: 1) detention must avert greater harm (by preventing crime) than it inflicts (by depriving a person of liberty) and 2) prohibitions against pretrial punishment mean that the harm experienced by the detainee cannot be discounted in the cost-benefit calculus. With this conceptual framework in place, we develop a novel empirical method for estimating the relative harms of incarceration and crime victimization that we call “Rawlsian cost-benefit analysis”: a survey method that asks respondents to choose between being the victim of certain crimes or being jailed for varying time periods. The results suggest that even short periods of incarceration impose grave harms, such that a person must pose an extremely high risk of serious crime in order for detention to be justified. No existing risk assessment tool is sufficient to identify individuals who warrant detention. The empirical results demonstrate that the stated consequentialist rationale for pretrial detention cannot begin to justify our current detention rates, and suggest that the existing system veers uncomfortably close to pretrial punishment. The degree of discord between theory and practice demands a rethinking of pretrial law and policy